Soft Sensing Image Analysis and Processing Method of Substation Equipment Defects - Banihashemi, Saeed; Zhang, Jingxiao (Bright Institute, 2023)
In the context of incentivizing regulation for distribution companies, the utilization of a reference network model proves to be a valuable tool for evaluating their effective cost. These models play a crucial role in planning expansive distribution areas that encompass various voltage levels. This paper introduces a green space planning algorithm designed to optimize the location, size, and power supply areas of medium and low voltage substations within the Reference Network Model (RNM). The algorithm aims to enhance the efficiency and environmental impact of these substations. The focus of this study extends to two key aspects: the creation of